Revolt against history postmodern historicity in the novels of Gina Apostol - Chavez, Diane Tricia S. (College of Arts and Letters, University of the Philippines Diliman, 2016)
Postmodern approaches to history have typically been projects of baring it as nothing more than collated fictions whose meanings are contingent upon historians. It is curious, then, that postmodernism would be the driving principle behind historiographic fictions, which, for all that they move away from the rigid structures of historicism, are still guided by a sense of history. Using the novels of Gina Apostol, this study will look into the reconciliation of postmodernity with history, exploring how a nation can and must have a sense of pastness that dos not limit itself within the confines of historicism. The study will explore these three historiographic novels: The Revolution according to Raymundo Mata, Gun Dealers' Daughter, and Bibliolepsy - all set in the 1896 and the 1986 revolutions. Guided by Ashis Nandy's concept of a historical narratives and Pierre Nora's sites of memory, the study aims to show how the novels use postmodern strategies to achieve narratives that are rooted in history but not caged by it.